(3GdQhVI GdHgjI aj TQM GddeYI GdOeTbjIs - (3GdYGedj, GdLYHj, YR GdOjf, Rjf GdOjf Hf Ydj Hf CMeO, J (B966(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj TQM UOhQfG HdeYI ef TQGFY GdESdGe cGajI aj HjGf GdNWGH(B... (3hHYO agPg JYdjbI dWjaI(B...(3CVaJgG Edi GdeNJUQ GdTQja(B... (3GdehShe HGddeYI GdOeTbjIs
(3BNQgG (B:s
(3hjfHZj Cf jSJKfi ef Pdc eG jSJdRe GdVQQ hGdML Ohf ZjQg hCeG GSJKfGA GdeYLhR Yfg ahGVM(B. (3Je GdeLdO GdChd ef GddeYI GdOeTbjI eY TQMg Ydjg GdQhVI GdHgjI hjJdhg cJGH GdfcGMs
(3JHUQI GdeDda (B:s
(3GdTgjQ HGdTgjO GdKGfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B3(3, U(B64s
(3GdPQjYI, HQbe(B: 1757s
(3EjVGM Gdecfhf(B: (3L(B1(3, (B593s
Keywords: (3abg GdePGgH GdCNQis